Telaah Media Online dalam Proses Belajar Mengajar (Pbm) Pendidikan Agama Islam (Pai) di Era Pandemi Covid-19 - Nanang Budianto; Mukhsin Mukhsin (FALASIFA : Jurnal Studi Keislaman, 2021)
Learning Islamic Religious Education (PAI) in schools still requires improvement both technically, teaching methods, media and those related to the Islamic Religious Education Teaching and Learning Process (PAI) in schools, when the world is faced with a pandemic that hits. The Covid-19 VIRUS outbreak has an impact on learning Islamic Religious Education (PAI) in schools starting from the PAUD level to the SMA / MA / SMK level. This condition forces the education world to carry out the learning process online (online). The purpose of writing this article is to study and understand the use of online media in the Teaching and Learning Process of Islamic Religious Education (PAI) during the Covid-19 Pandemic. The use of online media during the Covid-19 pandemic caused various responses and impacts and changes in the learning system that could affect the Teaching and Learning Process (PMB) and the level of student development in responding to the material presented. Keywords: Use of online media, Field of Study PAI, Covid-19 pandemic. Pembelajaran Pendidikan Agama Islam (PAI) di sekolah masih memerlukan pembenahan baik secara teknis, metode pengajaran, media serta yang berkaitan dengan Proses Belajar Mengajar Pendidikan Agama Islam (PAI) di sekolah, ketika dunia dihadapkan dengan pandemi yang melanda. Wabah VIRUS Covid-19 memberikan dampak terhadap pembelajaran Pendidikan Agama Islam (PAI) di Sekolah mulai tingkat PAUD sampai dengan tingkat SMA/MA/SMK. Kondisi demikian memaksa dunia pendidikan melakukan proses pembelajaran secara daring (online). Tujuan penulisan artikel ini untuk mempelajari dan memahami penggunaan media online dalam Proses Belajar Mengajar bidang study Pendidikan Agama Islam (PAI) di masa Pandemi Covid-19. Penggunaan media online di masa pandemi covid-19 ini menimbulkan berbagai tanggapan serta dampak dan perubahan sistem belajar yang dapat mempengaruhi proses Proses Belajar Mengajar (PMB) serta tingkat perkembangan peserta didik dalam merespon materi yang disampaikan. Kata Kunci : Penggunaan media online, Bidang Study PAI, pandemi Covid-19.